⁠Dapsone Induced Methemoglobinemia in Pediatric Patient: A Case Report - Addyanto, Brian; Lukman, Leni (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Acquired methemoglobinemia is significantly more common than the congenital form, though it remains a rare condition. Most cases arise from accidental chemical exposure or the use of topical and local anesthetics. Case Description: We present a case of 14-year-old male presented with complaints of dark grayish discoloration of the skin on the face and hands, persisting for the past two months prior to admission. He was later diagnosed with dapsone induced methemoglobinemia. Patient was then discharged with oral therapy consisting of agents with antioxidant properties and instructed to discontinue dapsone consumption. Conclusions: In pediatric patients undergoing dapsone therapy, the risk of dapsone induced methemoglobinemia should be carefully considered to ensure early identification and prompt management, thus minimizing the potential for severe complications.